Landscapes of development - Berk, Laura E. (Wadsworth Publishing, 1999)
In this engaging anthology, each chapter presents an article that focuses on a different child development issue. Using the cross-cultural approach, this reader explores child development in many cultures and offers aspects of early childhood through adolescent development. The articles themselves are the focus, unlike many readers which use quotations from articles with editorial narrative to explain the material to the student. Each article offers a theory or application about child development